2016
DOI: 10.2337/dc16-0406
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study of Metformin and Sitagliptin on Long-term Normoglycemia Remission in African American Patients With Hyperglycemic Crises

Abstract: OBJECTIVEAfter intensive insulin treatment, many obese African American patients with new-onset diabetic ketoacidosis (DKA) and severe hyperglycemia are able to achieve near-normoglycemia remission. The optimal treatment to prevent hyperglycemic relapses after remission is not known.RESEARCH DESIGN AND METHODSThis prospective, 4-year, placebo-controlled study randomly assigned 48 African American subjects with DKA and severe hyperglycemia to metformin 1,000 mg daily (n = 17), sitagliptin 100 mg daily (n = 16),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…With intensive insulin treatment, ketosis-resistant patients also achieve near-normoglycemia remission from insulin (11,12,27). Our group along with McFarlane et al showed that similar remission from insulin occurs in obese AA patients who present with severe hyperglycemia (glucose levels >400 mg/dL) without the presence of ketoacidosis (11,12,21,26). …”
Section: Clinical Presentationsupporting
confidence: 51%
See 4 more Smart Citations
“…With intensive insulin treatment, ketosis-resistant patients also achieve near-normoglycemia remission from insulin (11,12,27). Our group along with McFarlane et al showed that similar remission from insulin occurs in obese AA patients who present with severe hyperglycemia (glucose levels >400 mg/dL) without the presence of ketoacidosis (11,12,21,26). …”
Section: Clinical Presentationsupporting
confidence: 51%
“…We and others have shown that treatment with sulfonylureas can prolong the period of near-normoglycemia remission (25,41). More recently, we also showed that treatment with metformin or sitagliptin is equally efficacious in prolonging near-normoglycemia remission (21). We studied 48 AA patients who presented with severe hyperglycemia and DKA and randomized the patients who achieved remission from insulin to metformin, sitagliptin, or placebo.…”
Section: Maintaining Near-normoglycemia Remissionmentioning
confidence: 96%
See 3 more Smart Citations